Com a palavra, as crianças: os sentimentos de alunos e alunas da primeira série do Ensino Fundamental - Saud, Claudia Maria Labinas Roncon (2005)
Abstract The affective dimension in the process teach-learning was emphasized in the present study which had as objective to know the schoolboys and schoolgirls feelings of the first grade of the elementary school in relation to the experiences lived in this context as well as identifying its provoking situations. The collection of data was made by na interview, prioritizing the schoolchildren s opinions from two classrooms of first grade of a private school, in a city of the state of São Paulo. The selection of the participants was made by choosing them by reffle divided in four groups of four children each one. For analysis and discussion of the data it was used the theoretical referencial of Henri Wallon. The results showed the presence of positive and negative3 feelings in relation to different referring provoking situations: to the teacher, to the test, to the break, to the arrival and departure of the students, to the subjects and to the first grade itself. It was concluded that the participants presented much more positive feelings than negative ones in relation to the experience in the first grade. The negative feelings indicate that it s needed to rethink some provoking situations so that, more and more, to correspond to the necessities, possibilities and characteristics of the children. Listening to them will help the educators in this task to rethink the conditions of education.